Smart Traffic Light Monitoring System for Emergency using Arduino - Kai Kee, Low; Attar Bashi, Zainab Senan (Multidisciplinary Applied Research and Innovation, 2021)
The popularity of private cars has increased the number of vehicles on the road day by day, which has led to a dramatic increase in traffic. Hence, traffic congestion has become a common phenomenon nowadays. This can cause a lot of problems, especially in emergency situations where the traffic at intersections is always busy. Whether it is an ambulance, a fire engine or a police car, traffic jams and delays are often encountered during emergency operations or rescue. Accidents between emergency vehicles and other vehicles also often occur at busy intersections when there is no emergency route for emergency vehicles because other vehicles must be crowded to provide special routes for emergency vehicles. Therefore, there is a need for a traffic light system that prioritizes emergency vehicles and dynamically adapts changing traffic conditions. In this project, a prototype of a traffic light system that consider emergency vehicles as priority was created based on Internet of Things (IoT) technology. The traffic light prototype was implemented using Arduino Uno with radio frequency (RF) transmission with 433 MHz RF modules. The traffic light system works normally until it receives a signal from an emergency vehicle, the lights sequence will change to help emergency vehicles pass the busy traffic junction fast. To evaluate the significance of the system, a survey was made to evaluate the usability and usefulness of the prototype. The findings showed that the system can be useful to increase the efficiency of emergency vehicles during emergency operation. In future, this prototype system can be improved to adapt to the actual traffic conditions by studying its limitations. Different modules or equipment can be used in a real-life scenario to improve the prototype.